Loss of vitamin A in fortified edible oils and ghee during cooking in asian traditional style (Bangladesh Journal of Scientific and Industrial Research, 2012)
Vitamin 'A' is essential for normal growth and its deficiency causes night blindness, affects the regulatory function of skin and reduces the    general resistance of organism to infection. This deficiency does not occur by using balanced diet or by fortification of staple food with appropriate amount of Vitamin 'A'. In Pakistan vitamin 'A' fortification is done in vegetable ghee/cooking oil. It is generally assumed that  fortified amount of vitamin 'A' is fully destroyed when the food is cooked at high temperature. The present study was focused to examine the effect of Pakistani traditional cooking style on the degree of destruction of vitamin 'A' mandatory fortified in the vegetable ghee/ cooking oils. The study indicates that there are some losses of Vitamin A of the fortified oils during cooking. However in case of deep fat frying destruction of added vitamin 'A' is more pronounced. The loss of vitamin 'A' was less than 50%,  when the food was cooked in Pakistani style in case of all the cooking oils/ vegetable ghee. In prolonged frying conditions substantial amount of vitamin 'A' (45%) remains in the oil. Any how, this retention of vitamin 'A' is sufficient to meet the body requirements when oils/ghee was fortified according to the prescribed Pakistan Pure Food Rules 1965 i.e. 33,000 IU per Kg.   DOI: http://dx.doi.org/10.3329/bjsir.v47i2.11461   Bangladesh J. Sci. Ind. Res. 47(2), 243-248, 2012